The Dynamic Concept for Waste Pile Prediction in Bogor City - Adelia Rizki Widyasandra; Deffi Ayu Puspito Sari; Ernalem Bangun (CV. AFDIFAL MAJU BERKAH, 2024)
Areas with high population density have the potential to degrade environmental quality. This is because an increase in population leads to a higher amount of waste accumulation. Bogor City is known for its dense population. In 2018, the Galuga Bogor Landfill received 650 tons of waste per day. With the population growing each year, accompanied by an increase in waste generation, there is a need for effective and sustainable waste management efforts. However, several obstacles are often encountered in waste management, such as the lack of understanding among the population. If left unaddressed, this situation can have serious implications for the environment, leading to natural disasters and public health issues. The aim of this research is to predict the amount of waste accumulation in Bogor City, with the hope of assisting the government and the community in enhancing waste management practices. The research methodology involves the analysis of Causal Loop Diagram (CLD) and Stock Flow Diagram (SFD), which will be simulated using Time Graph and Time Table, and processed through the Powersim Studio 10 Express application. Simulation results indicate that waste accumulation in Bogor City is expected to continue increasing from 2018 to 2025. The difference in waste accumulation between 2018 and 2025 is estimated to be 87,783 tons, with the Bogor City Landfill projected to receive 890 tons of waste per day by 2025.